Effect of hot metal charging on economic and environmental indices of electric arc furnace steelmaking in China. (15th December 2022) - Tian, Bohan; Wei, Guangsheng; Li, Xin; Zhu, Rong; Bai, Hao; Tian, Weijian; Dong, Kai
Abstract: Hot metal (HM) charging electric arc furnaces (EAF) with good production indices and economic benefits have been widely used in China. In this study, the economic and environmental indices of EAF were analyzed based on a mechanistic process model, and the energy consumption, carbon emissions, and production costs with different hot metal ratios (HMRs) were obtained. There are strong correlations between HMR and the energy consumption, carbon emissions, and production costs of EAF. The Pareto optimal solution for the current state is 50% HMR-EAF, which produces carbon emissions of 1402.68 kg-CO2 /t and a production cost of 3609.40 CNY/t. Considering the current situation in China, this process is more in line with the need to coordinate the economic and environmental indices of steel plants compared to direct reduced iron (DRI)-EAF, scrap-EAF, and blast furnace-basic oxygen furnace (BF-BOF) processes. Moreover, it has the potential to be more easily realized and promoted.